KVALITATIVNE PROMJENE SITUACIONO - MOTORIČKIH SPOSOBNOSTI NOGOMETAŠA POD UTICAJEM PROGRAMA NOGOMETA - Osmo Bajrić; Midhat Mekić; Senad Bajrić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
This research work was carried out on the sample group of 137 football players, 14 to 16 years of age (cadets) , registered members of football clubs in the area of Srednjobosanski canton, Federation of Bosnia and Herzegovina. The research applies a set of 12 tests of situational-motoric abilities, which determine the shooting accuracy, ball-handling, dribbling speed, curved running speed and the force used to hit the ball. The basic aim of the research was to determine the qualitative changes of situational- motoric abilities that developed as a result of the programmed training activities. The analysis of possible changes (differences) between the initial and final measurements of situational-motoric abilities has been performed using factor analysis - model of congruation. On the basis of obtained values of factor analysis as part of the model of congruation it can be concluded that the football programme has partially influenced the qualitaive changes of situational-motoric abilities.